2018
DOI: 10.1038/s41598-018-19193-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum ω-3 Polyunsaturated Fatty Acids and Potential Influence Factors in Elderly Patients with Multiple Cardiovascular Risk Factors

Abstract: Recent clinical trials failed to demonstrate that ω-3 polyunsaturated fatty acid (PUFA) supplement reduced cardiovascular events, which contradicted previous evidence. However, serum ω-3 PUFA concentrations of participants remained unclear in those studies. We aimed to investigate the definite relationship between serum concentrations of ω-3 PUFAs and coronary artery disease (CAD), and to explore the potential influence factors of ω-3 PUFAs. We selected Chinese in-patients (n = 460) with multiple cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…A possible explanation for these phenomena is that oxidative stress and inflammation are implicated in ageing process, resulting in an antioxidant depletion. As for omega-3 PUFAs, most studies found a regular increase in EPA and DHA with rising age [28][29][30], others were not [21]. In general, aging has been proven to be relevant to nutritional status [31] and the correlations maybe more apparent after adjustment for varied dietary intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for these phenomena is that oxidative stress and inflammation are implicated in ageing process, resulting in an antioxidant depletion. As for omega-3 PUFAs, most studies found a regular increase in EPA and DHA with rising age [28][29][30], others were not [21]. In general, aging has been proven to be relevant to nutritional status [31] and the correlations maybe more apparent after adjustment for varied dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting plasma samples were collected and stored at -80℃ until analyses. Plasma EPA, DHA, α-, γ-, and δ-tocopherol were measured by LCMS as we declared in previous article [21] (Fan-Xing Biological Technology-Beijing Co., Ltd). The peak area of each component was linearly correlated with its concentration (R 2 > 0.99).…”
Section: Measurement Of Omega-3 Pufas and Tocopherolsmentioning
confidence: 99%
“…Mozaffarian et al demonstrated that total plasma concentration of ω‐3 FAs was found to be associated with lower incidence of heart failure in older adults. Furthermore, a cross‐sectional study in a Chinese population found a lower level of serum ω‐3 FAs in CHD than that in patients with cardiovascular risk factors . Several long‐term clinical trials are ongoing and the results are expected in the near future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
“…Determination of the beneficial effect producing blood level of ω‐3 FA in various pathological conditions may be considered for a consistent result . Liu et al demonstrated that the serum level of ω‐3 FA may be affected by the intake of alcohol or drugs like proton pump inhibitors. Mozaffarian et al demonstrated that total plasma concentration of ω‐3 FAs was found to be associated with lower incidence of heart failure in older adults.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…N-3 polyunsaturated fatty acids (n-3PUFAs) is the essential fatty acids, which has the effect of resisting obesity, lowering blood glucose, lowering blood fat and anti inflammation [12] . However, animal supplements n-3 PUFAs can only by eating deep-sea fish and other means.…”
Section: Introductionmentioning
confidence: 99%